Prognostic value of an inflammatory index for patients with metastatic castration‐resistant prostate cancer. Issue 7 (5th March 2020) - Yamada, Yasutaka; Sakamoto, Shinichi; Rii, Junryo; Yamamoto, Satoshi; Kamada, Shuhei; Imamura, Yusuke; Nakamura, Kazuyoshi; Komiya, Akira; Nakatsu, Hiroomi; Ichikawa, Tomohiko
Abstract: Background: The inflammatory process has been reported to be involved in the formation and progression of various types of cancer. Recently, a peripheral inflammatory index, combining the derived neutrophils/(leukocytes minus neutrophils) ratio (dNLR) and the lactate dehydrogenase (LDH) level, was proposed as a useful prognostic marker in advanced nonsmall cell lung cancer. The prognostic value of inflammatory markers in prostate cancer has not been established. We aimed to validate the prognostic significance of this peripheral inflammatory index in metastatic castration‐resistant prostate cancer (mCRPC). Methods: Clinical data of 196 mCRPC patients were retrospectively collected from multiple institutions. Clinical factors and inflammatory markers at the development of CRPC, including white blood cell count, absolute neutrophil count, dNLR, neutrophil‐lymphocyte ratio, platelet‐lymphocyte ratio, C‐reactive protein (CRP), and LDH levels, were evaluated. The patients were classified into three groups based on the inflammatory index: Good (low dNLR and LDH), Intermediate (high dNLR or LDH), and Poor (high dNLR and LDH). Overall survival (OS) and cancer‐specific survival after CRPC were analyzed using Cox proportional hazard models and Kaplan‐Meier methods. Results: The median age and baseline prostate‐specific antigen level were 75 years and 397.15 ng/mL, respectively. On multivariate analysis, dNLR (≥1.51; hazard ratio [HR] = 1.624; P = .0173), LDH (≥upper limit of normal; HR = 2.065; P = .0004), alkaline phosphatase (≥310 U/L; HR = 2.546; P < .0001), and positive N stage (HR = 1.621; P = .048) were associated with poor OS after CRPC, whereas other inflammatory markers including the NLR were not. The Good inflammatory index group showed significantly longer OS after CRPC compared to the Intermediate and Poor groups, with median survivals of 46.2, 28.9, and 16.6 months, respectively. Conclusions: The novel inflammatory index combining dNLR and LDH was a useful prognostic parameter in patients with mCRPC. Our analysis suggested that dNLR emerged as a more valuable prognostic marker than NLR.